2017
DOI: 10.21511/bbs.12(3-1).2017.08
|View full text |Cite
|
Sign up to set email alerts
|

Performance differences between Islamic and conventional banking forms

Abstract: AUTHORSTurki Alshammari ARTICLE INFOTurki Alshammari (2017 AbstractThis paper strives to recognize the possible performance differences between the two popular banking forms in the Gulf Cooperation Council (GCC) countries. Applying different methodologies on the data that span the period 2003-2015, this study documents significant differences with respect to the period, countries, and performance measures. Specifically, conventional banks in GCC countries outperform their Islamic counterparts in profitability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
2
10
0
1
Order By: Relevance
“…Furthermore, the correlation between NPF and ROA results in a negative relationship so that an increase in NPF will reduce the profitability of Islamic banking (Santoso et al, 2019). At the same time, NPF correlation with ROA is positive and will improve efficiency (Santosa, 2011;Alshammari, 2017;Dahir et al, 2019).…”
Section: The Correlation Between Rgec and Non-performing Financingmentioning
confidence: 99%
“…Furthermore, the correlation between NPF and ROA results in a negative relationship so that an increase in NPF will reduce the profitability of Islamic banking (Santoso et al, 2019). At the same time, NPF correlation with ROA is positive and will improve efficiency (Santosa, 2011;Alshammari, 2017;Dahir et al, 2019).…”
Section: The Correlation Between Rgec and Non-performing Financingmentioning
confidence: 99%
“…Turki Alshammari in his 2017 study (Alshammari 2017) found that the 2008 subprime crisis affected the performance of CBs, but not the IBs in Saudi Arabia, Kuwait, and United Arab Emirates. Mollah et al (2017) examined whether the difference in governance structures influences the performance of Islamic banks compared to commercial banks.…”
Section: Review Of Literaturementioning
confidence: 99%
“…While the ROE of GCC conventional banks averages 11.3%, it is almost 8.6% for GCC Islamic banks (which supports the argument of Alshammari, 2017). Third, Islamic banks seem to have riskier portfolios than those of GCC conventional banks.…”
Section: Resultsmentioning
confidence: 53%